THE PLACE OF BEHBUDI IN CENTRAL ASIAN JADIDISM (Universal International Scientific Journal, 2026)
This article is devoted to the life and scientific and political activities of Mahmudkhodja Behbudi, the father of the Central Asian Jadids. It also analyzes his travels published in the magazine "Oyina", his meetings with Ismail Gasprinsky, and his conversations with colleagues.
Keywords: "Oyina" magazine, qori, madrasa, volost, geography, deputy, mudarris, imam.